2014
DOI: 10.1088/1748-3182/9/4/046017
|View full text |Cite
|
Sign up to set email alerts
|

A lifting line model to investigate the influence of tip feathers on wing performance

Abstract: Bird wings have been studied as prototypes for wing design since the beginning of aviation. Although wing tip slots, i.e. wings with distinct gaps between the tip feathers (primaries), are very common in many birds, only a few studies have been conducted on the benefits of tip feathers on the wing's performance, and the aerodynamics behind tip feathers remains to be understood. Consequently most aircraft do not yet copy this feature. To close this knowledge gap an extended lifting line model was created to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…When it comes to stability and control considering bird wing tips, only the yawing moment of bird feather found some attention, but very few studied the effect of the pitching and rolling moments. The mathematical model available for an airplane in the form of lifting line theory is not yet developed for bird flight except what has been done by Fluck (2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to stability and control considering bird wing tips, only the yawing moment of bird feather found some attention, but very few studied the effect of the pitching and rolling moments. The mathematical model available for an airplane in the form of lifting line theory is not yet developed for bird flight except what has been done by Fluck (2014).…”
Section: Resultsmentioning
confidence: 99%
“…During each half-stroke total force production produces a force that supports 115% of body weight, and during upstroke force is generated at 36% of body weight. According to Fluck and Crawford (2014), an increase in wing efficiency by splitting the wing tip like birds feather wingtip is possible and found that the best performance can be achieved through spreading the wing tip like the spreading of feathers over a large angle of the wing planform. Hua et al (2014) have shown that bionic wing aerodynamics performance is superior to the conventional airfoil wing.…”
Section: Bird Feather Tip For Drag Reduction Researchmentioning
confidence: 99%
“…Fluck and Crawford [26] created an extended lifting line model considering the viscous drag effect to calculate the lift distribution, and drag of wings varying with cant angles, tip twist angle and number of wingtip slots, (Fig. 13).…”
Section: Numerical Simulations On Bionic Slotted Wingsmentioning
confidence: 99%
“…It was found that slotted wings with appropriate Fig. 13 The is bird wing compared with the simplified wing in the bird wing for the lift line model [26] Fig. 14 Lift-to-drag ratio and drag polar for an elliptic wing versus base wing with five twisted feathers [26] Fig.…”
Section: Wind Tunnel Experiments On Bionic Slotted Wingsmentioning
confidence: 99%
“…However, repeatedly solving this equation for multiple candidate designs is still fairly costly, even for an aerodynamic model as simple as BEM. A more complicated aerodynamic model (eg, a Lagrangian vortex model as would be used to analyze advanced blade geometries) might not allow to express blade loads explicitly as a function of the random variable. Hence, the next section presents the steps necessary to project Equation onto the stochastic space.…”
Section: Methodsmentioning
confidence: 99%